Delayed payment schemes in Central-Eastern Europe and Middle-East - Ádám, Ildikó; Callenbach, Marcelien; Németh, Bertalan; Vreman, Rick A.; Pontén, Johan; Strbad, Tea; Dawoud, Dalia; Kostyuk, Alexander; Seyam, Ahmed; Nagy, László; Goettsch, Wim G.; Kaló, Zoltán (Frontiers in Medicine, 2022)
The need for innovative payment models for health technologies with high upfront costs has emerged due to affordability concerns across the world. Early technology adopter countries have been experimenting with delayed payment schemes. Our objective included listing potential barriers for implementing delayed payment models and recommendations on how to address these barriers in lower income countries of Central and Eastern Europe (CEE) and the Middle East (ME). We conducted a survey, an exploratory literature review and an iterative brainstorming about potential barriers and solutions to implement delayed payment models in these two regions. A draft list of recommendations was validated in a virtual workshop with payer experts from the two regions. Eight barriers were identified in 4 areas, including transaction costs and administrative burden, payment schedule, information technology and data infrastructure, and governance. Fifteen practical recommendations were prepared to address these barriers, including recommendations that are specific to lower income countries, and recommendations that can be applied more universally, but are more crucial in countries with severe budget constraints. Conclusions of this policy research can be considered as an initial step in a multistakeholder dialogue about implementing delayed payment schemes in CEE and ME countries.